CRISPR-Cas9 human gene replacement and phenomic characterization in Caenorhabditis elegans to understand the functional conservation of human genes and decipher variants of uncertain significance - Troy A. McDiarmid; Vinci Au; Aaron D. Loewen; Joseph Liang; Kota Mizumoto; Donald G. Moerman; Catharine H. Rankin (The Company of Biologists, 2018)
Our ability to sequence genomes has vastly surpassed our ability to interpret the genetic variation we discover. This presents a major challenge in the clinical setting, where the recent application of whole-exome and whole-genome sequencing has uncovered thousands of genetic variants of uncertain significance. Here, we present a strategy for targeted human gene replacement and phenomic characterization, based on CRISPR-Cas9 genome engineering in the genetic model organism Caenorhabditis elegans, that will facilitate assessment of the functional conservation of human genes and structure-function analysis of disease-associated variants with unprecedented precision. We validate our strategy by demonstrating that direct single-copy replacement of the C. elegans ortholog (daf-18) with the critical human disease-associated gene phosphatase and tensin homolog (PTEN) is sufficient to rescue multiple phenotypic abnormalities caused by complete deletion of daf-18, including complex chemosensory and mechanosensory impairments. In addition, we used our strategy to generate animals harboring a single copy of the known pathogenic lipid phosphatase inactive PTEN variant (PTEN-G129E), and showed that our automated in vivo phenotypic assays could accurately and efficiently classify this missense variant as loss of function. The integrated nature of the human transgenes allows for analysis of both homozygous and heterozygous variants and greatly facilitates high-throughput precision medicine drug screens. By combining genome engineering with rapid and automated phenotypic characterization, our strategy streamlines the identification of novel conserved gene functions in complex sensory and learning phenotypes that can be used as in vivo functional assays to decipher variants of uncertain significance.